Dampak Penggunaan Media Sosial Terhadap Perilaku Belajar Peserta Didik - Alifa Dara Kasih; Faiza Dwi Putri; Denisa Tri Puji Astuti; Mulya Maharani (INDO PUBLISHING, 2026)
The development of information and communication technology in the digital age has made social media an integral part of people’s daily lives, particularly among students. This study aims to analyze the impact of social media use on students’ learning behavior and academic achievement based on a systematic review of various recent studies. The approach used in this article is a descriptive quantitative approach. The findings indicate that the intensity of social media use has a significant influence on students’ discipline, motivation, and learning outcomes. Although social media offers easy access to information and collaboration, excessive use tends to result in poor academic performance, reduced focus, and poor time management.